Civil war and natural resources: a quantitative approach - Falcao de Jesus, Manuel Jose Romao Xavier (Kansas State University, 2009)
This study is an effort to shed some light on the causes of civil war. The literature on civil war onset has been framed under three main perspectives: cultural, political and economic approaches. Recent studies, however, tend to narrow the debate and posit explanations for civil war as either greed-motivated or grievance-motivated. This study replicates one of the most prominent econometric models on civil war, the Collier and Hoeffler model (CH), and further validated their economic interpretation of civil war as greed-motivated. Their argument is that greed-led behavior is motivated by an abundance of valuable resources. However, Collier and Hoeffler overlooked one critical element: scarce resources also contribute to discontent and violent protests. This study suggests that the CH model should include resource scarcity to avoid omitting variable bias.
Keywords: civil war; natural resources; collier-hoeffler model; resource abundance; resource scarcity; Political Science, General (0615)